2011
DOI: 10.1111/j.1365-4632.2011.05015.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and tolerability of tacrolimus 0.03% ointment in infants:* a two‐year open‐label study

Abstract: Over a period of two years, tacrolimus 0.03% ointment was associated with substantial clinical improvement of AD in infants aged <2 years. Treatment tolerability was similar to that seen in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 14 publications
2
28
0
2
Order By: Relevance
“…The combined mean improvement for the cohort was 63.9%; responders averaged 84.1% improvement and partial to nonresponders averaged 21.7% improvement. While differing in clinical scoring approaches, these results are consistent with previous open-label phase II studies on currently approved topical calcineurin and PDE-4 inhibitors (26,27). In this trial, all adult patients who appeared responsive to treatment reported sustained or even additional clinical improvement after the washout phase ( Figure 2, D and E).…”
Section: R Mucosa Was Associated With Clinical Improvement and Safetsupporting
confidence: 80%
“…The combined mean improvement for the cohort was 63.9%; responders averaged 84.1% improvement and partial to nonresponders averaged 21.7% improvement. While differing in clinical scoring approaches, these results are consistent with previous open-label phase II studies on currently approved topical calcineurin and PDE-4 inhibitors (26,27). In this trial, all adult patients who appeared responsive to treatment reported sustained or even additional clinical improvement after the washout phase ( Figure 2, D and E).…”
Section: R Mucosa Was Associated With Clinical Improvement and Safetsupporting
confidence: 80%
“…The efficacy of long‐term monotherapy with tacrolimus ointment has been shown in children and adults . Less data are available for children under 2 years of age . Pimecrolimus cream has been studied in infants and children in a combination regimen with TCS, the latter being given if a flare occurred.…”
Section: Topical Anti‐inflammatory Treatmentmentioning
confidence: 99%
“…In addition, there are substantial differences in the number of patients studied (and duration of treatment) with each drug (Table 3) [63, 81, 116–118]. At the time of approval, pimecrolimus cream had been studied in more pediatric patients, including infants, for significantly longer durations, yet the indications for both drugs in these regards are remarkably similar.…”
Section: Critical Evaluation Of the Evidencementioning
confidence: 99%